Ultrasound microbubble-mediated miR-503–5p downregulation suppressed in vitro CRC progression via promoting SALL1 expression. (June 2022) - Wang, Yaru; Li, Yanting; Li, Xin
Abstract: Background: This study compared the effect of ultrasound microbubble-mediated miR-503–5p downregulation with that of pure liposome-mediated miR-503–5p downregulation on colorectal cancer (CRC) progression and explored the downstream mechanism. Methods: Bioinformatics tools were utilized to predict miR-503–5p-targeted genes and CRC progression-associated genes. MiR-503–5p and sal-like 1 (SALL1) expressions in CRC cells and tissues were analyzed by qRT-PCR and/or bioinformatics tools; their correlations with overall survival and clinicopathological features of CRC patients were presented, and their interaction was validated by dual-luciferase reporter assay. CRC cells received ultrasound microbubble-mediated miR-503–5p downregulation and/or liposome-mediated miR-503–5p downregulation or SALL1 silencing. Cell phenotype changes were evaluated by flow cytometry, as well as MTT, Wound healing, Transwell and tube formation assays. E-cadherin, N-cadherin, Vimentin, B-cell lymphoma (Bcl)− 2, Cleaved caspase-3, and SALL1 expressions in cells were analyzed by Western blot. Results: Upregulated miR-503–5p in CRC tissues and cells was detected, associated with poorer cell differentiation, easier lymph node metastasis and higher TNM stages, and related to poorer prognoses of CRC patients. Ultrasound microbubble-mediated miR-503–5p downregulation relative to pure liposome-mediated miR-503–5p downregulation better decreased viability, inhibited migration, invasion and tube formation, enhanced apoptosis, upregulated SALL1, E-cadherin and Cleaved caspase-3, and downregulated miR-503–5p, N-cadherin, Vimentin and Bcl-2 in CRC cells. SALL1 was targeted by miR-503–5p, low-expressed in CRC tissues and cells and positively related to CRC patients' survival. Silencing SALL1 exerted the opposite effects, which reversed the effects of ultrasound microbubble-mediated miR-503–5p downregulation and vice versa. Conclusion: Ultrasound microbubble-mediated miR-503–5p downregulation suppressed in vitro CRC progression via promoting SALL1 expression. Highlights: Pure liposome-mediated miR-503–5p downregulation suppressed CRC progression. Ultrasound microbubble (UMB)-mediated transfection better downregulated miR-503–5p. UMB-mediated miR-503–5p downregulation better suppressed CRC progression. SALL1 was targeted by miR-503–5p and low-expressed in CRC tissues and cells. SALL1 silencing reversed the UMB-mediated miR-503–5p downregulation-induced effect.